ROLE OF EMPLOYEE COMPETENCE AND JOB AUTONOMY ON EMPLOYEE INNOVATIVE BEHAVIOR IN THE OIL AND GAS SECTOR IN DELTA STATE - KPEKPEDUKE, GABRIEL EGHAGHA; ASIEGBU, IKECHUKWU F., (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
It has been observed that insufficient attention has been given to the link between employee empowerment proxies and their innovative behavior, especially in the oil and gas sector. Drawing on the resource-based view theory, this study explored the influence of two proxies of employee empowerment - employee competence and job autonomy, on innovative behavior. Primary data were collected from one hundred and twenty (120) staff of oil and gas firms in Delta State, while simple regression was employed for data analyses. The study revealed that employee competence and job autonomy have a positive impact on their innovative behavior. The study, therefore, concludes that both employee competence and job autonomy enhance their innovative behavior. The recommendation is that Oil and gas firms in Delta State that are desirous of enhancing innovative behavior of their employees should first increase their psychological empowerment by enhancing their employee competence and job autonomy, which, in turn, can be achieved through appropriate skill and knowledge training.